2019
DOI: 10.5089/9781513513768.001
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomic Effects of Labor and Product Market Reforms in Morocco

Abstract: This paper studies the macroeconomic effects and sequencing of (LMRs) and product (PMRs) market reforms in Morocco. It finds that introducing LMRs and PMRs simultaneously would add about 2.5 percentage points (pp) of GDP growth and reduce unemployment by about 2.2 pp after five years. If sequencing is required, starting with PMRs would be more effective in boosting output, while starting with LMRs would reduce unemployment faster. Finally, increasing unemployment benefits would be more effective if this reform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Studies found that product and labor market deregulation reduces and redistributes rents (through the effects on entry costs, the degree of competition, and the bargaining power of workers), and therefore boosts aggregate labor productivity and employment over the long term (Barnes et al, 2013;Bouis and Duval, 2011;Duval and Furceri, 2018;IMF, 2019). In the case of Morocco, well-designed market reforms could substantially increase output and employment in the medium term (Sarr et al, 2019).…”
Section: A Structural Indicatorsmentioning
confidence: 99%
“…Studies found that product and labor market deregulation reduces and redistributes rents (through the effects on entry costs, the degree of competition, and the bargaining power of workers), and therefore boosts aggregate labor productivity and employment over the long term (Barnes et al, 2013;Bouis and Duval, 2011;Duval and Furceri, 2018;IMF, 2019). In the case of Morocco, well-designed market reforms could substantially increase output and employment in the medium term (Sarr et al, 2019).…”
Section: A Structural Indicatorsmentioning
confidence: 99%
“…In the case of Morocco, well-designed labor market and product market reforms could substantially increase output and employment in the medium term (see Sarr, Benlamine, and Munkacsi 2019). Several studies suggest that long-term growth in emerging markets and developing economies stands to benefit significantly from governance reforms (Mo 2001;October 2019 World Economic Outlook).…”
Section: Morocco's Agenda Of Structural Reformsmentioning
confidence: 99%
“…More complex, DSGE models for the Morocco economy are already available, including the Morocco Policy Analysis Model (MOPAM) developed by Bank Al-Maghrib (BAM) also with IMF technical assistance (Achour et al 2021), and the model used in Sarr, Benlamine, and Munkacsi (2019). While gifted with a much richer structure, the complexity of these model makes them less usable for regular, more high frequency analysis of policy-relevant questions.…”
Section: Introductionmentioning
confidence: 99%